ANALYSIS OF THE INFLUENCE OF HUMAN DEVELOPMENT INDEX, ECONOMIC GROWTH, AND UNEMPLOYMENT ON POVERTY IN EAST JAVA - Yulianus Wawan; Erwan Aristyanto; Rodhiyah Rodhiyah; Pramandyah Fitah Kusuma (WORLDVIEW ( Development economic and sharia studies journal ), 2025)
The research aims to analyze how the Human Development Index, Gross Domestic Product Growth, and Unemployment Rate affect the Poverty Rate in East Java Province during the period 2017 - 2024. The research sample uses data from all districts and cities in East Java. It employs a quantitative method based on panel regression analysis with fixed effects panel data technique, which combines time series data with cross-sectional data, allowing for more efficient estimation and control for unobserved individual heterogeneity. The findings of the study indicate that all three independent variables significantly influence the poverty rate together. However, poverty is only significantly negatively impacted by economic expansion, at least to some extent. There is no statistically significant relationship between the Human Development Index and the unemployment rate, although the direction of the relationship aligns with economic theory. This result highlights the importance of developing inclusive economies as a strategy to reduce poverty in the region.